Common pitfalls of perioperative clinical trials in response to ‘Barriers and enablers to recruiting participants within paediatric perioperative and anaesthetic settings: lessons learned from a trial of melatonin versus midazolam in the premedication of anxious children (the MAGIC trial)’ - Tori N. Sutherland; Paul A. Stricker; Andrew J. Davidson (BJA Open)
Summary: In this issue, Hyslop and colleagues discuss challenges leading to inadequate enrolment and premature termination of the MAGIC trial, a multicentre randomised controlled trial of melatonin vs midazolam premedication for anxiety among children. The authors should be commended for sharing their experiences, as they underscore common pitfalls of well-intended trials in the perioperative setting, including issues with study design and implementation.